CCL8 secreted by tumor-associated macrophages promotes invasion and stemness of glioblastoma cells via ERK1/2 signaling - Zhang, Xiang; Chen, Lu; Dang, Wei-qi; Cao, Mian-fu; Xiao, Jing-fang; Lv, Sheng-qing; Jiang, Wen-jie; Yao, Xiao-hong; Lu, Hui-min; Miao, Jing-ya; Wang, Yan; Yu, Shi-cang; et al. (Laboratory investigation, 2020)
Tumor-associated macrophages (TAMs) constitute a large population of glioblastoma and facilitate tumor growth and invasion of tumor cells, but the underlying mechanism remains undefined. In this study, we demonstrate that chemokine (C-C motif) ligand 8 (CCL8) is highly expressed by TAMs and contributes to pseudopodia formation by GBM cells. The presence of CCL8 in the glioma microenvironment promotes progression of tumor cells. Moreover, CCL8 induces invasion and stem-like traits of GBM cells, and CCR1 and CCR5 are the main receptors that mediate CCL8-induced biological behavior. Finally, CCL8 dramatically activates ERK1/2 phosphorylation in GBM cells, and blocking TAM-secreted CCL8 by neutralized antibody significantly decreases invasion of glioma cells. Taken together, our data reveal that CCL8 is a TAM-associated factor to mediate invasion and stemness of GBM, and targeting CCL8 may provide an insight strategy for GBM treatment.